FRIEND FACTOR: UNVEILING STUDENTS' DIFFICULTY IN SPEAKING ENGLISH - Wardani, Marianka Nanda; Atin, Atin Kurniawati (Institut Agama Islam Negeri (IAIN) Bone, 2024)
This research aims to find out the students’ difficulties in English speaking, and the factors that make the students feel difficult in English speaking at the eleventh grade of SMA N 1 Gondang in academic year 2023/2024. This study used descriptive qualitative research as the method with the case study as the type of research design. The researcher chose SMA N 1 Gondang in XI A class as sample which consist of 26 students. In collecting data, the researcher used questionnaire and interview. The acquired data were analyzed utilizing data condensation, data display, and conclusion drawing. To demonstrate the data's trustworthiness, the researcher employed data triangulation. There are several types of difficulties faced by the students, namely inhibition, nothing to say, and mother tongue use. Inhibition includes the students afraid of making mistakes to speak English, feeling shy and nervous. Nothing to say includes lack of vocabulary and lack of grammar. Mother tongue use includes students’ habits of using mother tongue, and difference pronunciation. The factors of students’ difficulties in speaking English are internal and external factors. The internal factors are interest, ability to understand learning, and shy or nervous, meanwhile external factors are family environment, and student environment.Keywords: Students Difficulties, Speaking Skills